PERANAN KEPALA KAMPUNG DALAM PELAKSANAAN SISKAMLING - Atika Dwi Lestari; Irawan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2017)
The purpose of the research is to explain the role of the head of village within implementation of security enviroment systems in East Kotagajah village. The method used in this research is descriptive with quantitative approach, the subjects studied are citizens hamlet village IV East Kotagajah totaling 147 peoples. Samples taken is 25% or about 37 peoples. The data collection technique used was a questionnaire and interview and observation. The data analysis techniques used in this study is the formula of Chi Square. The results of this research there is a role of the head of village within implementation of security enviroment systems in East Kotagajah village including role category with 18 respondents (48.64%) of the 37 respondents and implementation of security enviroment systems in East Kotagajah village categorized quite good with a large percentage of 64.86% or about 24 respondents.Tujuan penelitian ini adalah untuk menjelaskan peranan kepala kampung dalam pelaksanaan siskamling di Kampung Kotagajah Timur. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kuantitatif, subyek yang diteliti merupakan warga dusun IV kampung Kotagajah Timur yang berjumlah 147 orang. Sampel yang diambil adalah sebesar 25% atau 37 orang yang tersebar secara acak. Teknik pengumpulan data yang digunakan adalah angket dan wawancara serta observasi. Teknik analisis data yang digunakan dalam penelitian ini adalah rumus Chi Kuadrat. Hasil penelitian terdapat peranan kepala kampung dalam pelaksanaan siskamling di kampung Kotagajah Timur dengan kategori berperan dalam pelaksanaan siskamling dengan 18 responden (48,64%) dari 37 responden dan dalam pelaksanaan siskamling di kampung Kotagajah Timur termasuk kategori cukup baik dengan besar persentase 64,86% atau 24 responden.Kata kunci : kepala kampung, pelaksanaan siskamling, peranan